Ätiologie und Pathophysiologie des Fibromyalgiesyndroms: aktualisierte Leitlinie 2017 und Übersicht von systematischen Übersichtsarbeiten sowie eine Übersicht über Studien zur Kleinfaserpathologie bei Subgruppen des FMS = Etiology and pathophysiology of fibromyalgia syndrome : updated guidelines 2017, overview of systematic review articles and overview of studies on small fiber neuropathy in FMS subgroups - Üçeyler, Nurcan; Schiltenwolf, Marcus (Der Schmerz, 2017)
Background: The regular update of the guidelines on fibromyalgia syndrome, AWMF number 145/004, was planned for April 2017.Methods: The guidelines were developed by 13 scientific societies and 2 patient self-help organizations coordinated by the German Pain Society. Working groups (n =8) with a total of 42 members were formed balanced with respect to gender, medical expertise, position in the medical or scientific hierarchy and potential conflicts of interest. A systematic search of the literature from December 2010 to May 2016 was performed in the Cochrane library, MEDLINE, PsycINFO and Scopus databases. Prospective population-based studies and systematic reviews with meta-analyses of case control studies were taken into consideration for the statements. Levels of evidence were assigned according to the classification system of the Oxford Centre for Evidence-Based Medicine version 2009. The statements were generated by multiple step formalized procedures. The guidelines were reviewed and approved by the board of directors of the societies engaged in the development of the guidelines. Results: Current data do not enable identification of distinct factors in the etiology and pathophysiology of fibromyalgia syndrome. Fibromyalgia syndrome can be associated with inflammatory rheumatic diseases, gene polymorphisms, life style factors (e.g. smoking, obesity and lack of physical activity), depressive disorders as well as physical and sexual abuse in childhood and adulthood. Conclusion: Fibromyalgia syndrome is most probably the end result of various pathogenetic factors and pathophysiological mechanisms.